Interrelations between process safety management elements - Aziz, H.A. (John Wiley and Sons Inc., 2017)
OSHA PSM standard has been established with 14 elements that define the management principles to control process hazards and protect the workplace. One of the key factors to the success of Process Safety Management (PSM) implementation is that each element comes as a component in an integrated PSM program. Although various kind of integrated safety management systems have been introduced, direct integration system between PSM elements was not extensively studied due to vague concept on interrelation between PSM elements. This also hampers efforts in designing and developing integrated system for PSM. In this study, the interrelation of critical PSM elements was analyzed based on objectives and information functional of the elements stipulated in OSHA PSM regulations. From the conducted analysis, all the critical elements are interrelated at least with other seven PSM elements. Among the elements, Process Hazard Analysis and Mechanical Integrity were identified to have the highest interrelations comprising of 12 interrelated PSM elements. The developed PSM matrix has systematically showed the interrelation of critical PSM elements that useful for the development of Integrated PSM system. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 74–80, 2017. © 2016 American Institute of Chemical Engineers